2020
DOI: 10.1515/cclm-2020-0781
|View full text |Cite|
|
Sign up to set email alerts
|

Age appropriate reference intervals for eight kidney function and injury markers in infants, children and adolescents

Abstract: ObjectivesThe use of kidney function and injury markers for early detection of drug-related glomerular or tubular kidney injury in infants, children and adolescents requires age-specific data on reference intervals in a pediatric healthy population. This study characterizes serum values for eight kidney function and injury markers in healthy infants, children and adolescents.MethodsA single center prospective observational study was conducted between December 2018 and June 2019. Serum samples from 142 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Some researchers established reference intervals in particular sections or populations in recent years. 14 , 15 In our research, including KIM-1, biomarkers of 176 participants’ age distributed evenly and considered healthily were detected for correlation analysis with age. It had a moderate correlation with age ( r =0.41), independent with gender, suggesting it is a common phenomenon in the population.…”
Section: Discussionmentioning
confidence: 87%
“…Some researchers established reference intervals in particular sections or populations in recent years. 14 , 15 In our research, including KIM-1, biomarkers of 176 participants’ age distributed evenly and considered healthily were detected for correlation analysis with age. It had a moderate correlation with age ( r =0.41), independent with gender, suggesting it is a common phenomenon in the population.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, van Donge et al did not show significant differences in the serum values of UMOD, NGAL, and KIM-1 between healthy boys and girls. 53 In contrast, Bennett et al 54 reported statistically significant higher values of uNGAL in girls than boys. A similar relationship was not observed for KIM-1 level.…”
Section: Discussionmentioning
confidence: 90%
“…This study did not show any NGAL and UMOD age-dependency. 53 Scherberich et al 22 showed similarity of uromodulin serum levels in adults and children. In the group of 190 healthy adult patients, the mean sUMOD level was 207 ng/ml, whereas in pediatric population of 443 patients it was 193 ng/ml, and the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…210 Recognition and quantification of adverse events of the kidney necessitate age-appropriate reference intervals of kidney function and injury markers. 211,212 Besides these preclinical models might offer add-on benefit (e.g. to separate the impact of asphyxia vs. hypothermia on PK).…”
Section: Endogenous Biomarkersmentioning
confidence: 99%